The Minister, the Nation and the School: the planning of Primary Education in the Aftermath of the Spanish Civil War (1939-1951) - Veci Lavín, Carlos (Historia y Memoria de la Educación, 2025)
This paper explores the relationship between politics and education in the Spanish post-war period, during the period of José Ibáñez Martín (1939-1951) in the Ministry of National Education of Franco's regime. Based on the documentation kept in the minister's personal archives, it describes his school plans. The emphasis is on his idea of the school as a nationalising institution for the working classes and of the teacher as an apostle at their service. Secondly, it analyses how the minister's plan, the material situation, the political ups and downs of Franco's state and the concerns of groups such as the regime's single party and the Church conditioned this teaching. The unpublished drafts of the Law on Primary Education (1945), in force for twenty years, provide an insight into this political situation. The Falangist viewpoint, traced from the documentation of, among others, the Minister Secretary General of FET y de las JONS, José Luis de Arrese, as well as that of the Catholic Church, reflected in the work of the Episcopal Commission for Religious Education and Catechesis and the material conserved in the Vatican archives, complete the analysis of the complicated process of a law that was intended to solve all the problems of the school.